How do you solve -7n - 2n = 5+ 1- n - 7n7n2n=5+1n7n?

1 Answer
Oct 25, 2017

n=-6n=6

Explanation:

I'll try to do it step by step

-7n-2n=5+1-n-7n7n2n=5+1n7n

adding the nn's and the numbers in each side

-9n=6-8n9n=68n

the -8n8n goes to the other side as +8n+8n

-9n+8n=69n+8n=6

then we add the nn's in the left hand side

-n = 6n=6

multiplying in both sides by (-1)(1)

(-1)·(-n)=(-1)·6(1)(n)=(1)6

and finally

n=-6n=6

To prove we are right we change nn into -66 in the original ecuation.

(-7)·(-6) - 2·(-6) =5+1 -(-6)-7·(-6)(7)(6)2(6)=5+1(6)7(6)

and we get 36+12=6+6+3636+12=6+6+36 => 48=48 48=48

Since we get the equalty is true, the answer is correct.